(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Comparative Analysis: Heavy Metal Salts in Packaged Drinking Water Bottled drinking water is purified and packaged water that is sold in plastic or glass bottles for easy consumption on-the-go. Many people choose to drink bottled water because it is convenient, portable, and easily accessible.There are many brands and types of bottled water available on the market, ranging from natural spring water to purified and filtered tap water. Some bottled water may also be infused with vitamins, minerals, or electrolytes for added health benefits.While bottled water is a convenient option for staying hydrated, there are some environmental concerns associated with its production and disposal. Plastic bottles can contribute to pollution and harm wildlife when not disposed of properly. To reduce environmental impact, some companies are shifting towards more sustainable packaging options such as biodegradable bottles or refillable glass containers.Overall, bottled drinking water is a popular choice for many people who prioritize convenience and cleanliness in their hydration habits.Heavy metal salts are toxic substances that can have harmful effects on human health when consumed in high concentrations. These salts can leach into water sources from natural deposits or from industrial processes, leading to contamination of drinking water.